Development of Light weighted Optical Telescope Kit using Aluminum Profile and Isogrid Structure - 박우진; 이선우; 한지민; 안호재; 지태근; 김창곤; 김도훈; 이수민(경희대학교; 김영재; 김건희; 김정현; 김일훈; et al. (Journal of the Korean Astronomical Society, 55(1), 2022)
We introduce the Transformable Reflective Telescope (TRT) kit that applies an aluminum profile as a base plate for precise, stable, and lightweight optical system. It has been utilized for optical surface measurements, developing alignment and baffle systems, observing celestial objects, and various educational purposes through Research & Education projects. We upgraded the TRT kit using the aluminum profile and truss and isogrid structures for a high-end optical test device that can be used for prototyping of precision telescopes or satellite optical systems. Thanks to the substantial aluminum profile and lightweight design, mechanical deformation by self-weight is reduced to maximum 67.5~$μ$m, which is an acceptable misalignment error compared to its tolerance limits. From the analysis results of non-linear vibration simulations, we have verified that the kit survives in harsh vibration environments. The primary mirror and secondary mirror modules are precisely aligned within 50~$μ$m positioning error using the high accuracy surface finished aluminum profile and optomechanical parts. The cross laser module helps to align the secondary mirror to fine-tune the optical system. The TRT kit with the precision aluminum mirror guarantees high quality optical performance of 5.53~$μ$m Full Width at Half Maximum (FWHM) at the field center. KCI Citation Count: 0